Generalized Interpolative Contractions and an Application - Muhammad Nazam; Hassen Aydi; Aftab Hussain (Journal of Mathematics)
In this study, we introduce a property (P) and the generalized interpolative contractions of types I, II, III, and IV. We investigate certain conditions for the existence of fixed points of generalized interpolative contractions. We derive several new results from the main theorems. As an application, we resolve the Urysohn integral equation.